Three Essays on the Brand-Channel Interface: How Brand Equity Influences Distribution Channel Governance and Management - Kayed, Mohammad B. (My University, 2019)
In this dissertation, I explore some facets of the strategic interaction between brand equity and distribution channels. Specifically, I examine how brand equity influences the firm’s channel governance and channel management strategies. In this regard, I address the following two general research questions: (a) does a firm’s brand equity influence the way it governs its distribution channel? How? (b) Does a firm’s brand equity influence the way it manages its distribution channel? How? Using a wide assortment of archival data sources (e.g., Bond's Franchise Guide, Entrepreneur’s Franchise 500, Factiva, LexisNexis, University of Chicago’s Center for Research in Security Prices, Compustat, Statista, firms’ annual reports, Bloomberg and Wall Street Journal databases, and companies’ official websites), two large multi-year data sets, a variety of econometric techniques (e.g., Event Study, Multiple Regression, Probit, Multi-level Mixed-Effects Linear Models, Multinomial Logistic Regression, Generalized Linear Models, Multinomial Probit, Maximum Likelihood, Bayesian Panel Vector Autoregression), and drawing on several theories from marketing, economics, business law, and strategic management, I uncover some interesting strategic interactions taking place at the brand-channel interface. This dissertation comprises five chapters: three empirical studies (chapters 2, 3, and 4), an introduction, and a conclusion chapter. In the introduction chapter, I provide a snapshot of the current state of knowledge in the brand-channel interface research domain and illustrate how I situate this dissertation within that body of research. Besides, I provide a more nuanced view about the specific research questions each study addresses and a glimpse into the findings and implications of each study, as an entry to the dissertation. In chapter 2, using a large panel data set of North American, franchise-level annual observations for the period from 2001 to 2009, I assess the causal link between brand equity and channel governance structure, and discuss the managerial implications of this relationship in the areas of channel governance and capital allocation decision-making. In chapters 3 and 4, I stay within the same overarching theme of this dissertation and delve into a business phenomenon taking place at the brand-channel interface – gray markets. Despite the interdisciplinary research interest in gray markets, it remains one of the least empirically researched topics in business management due to the well-known data accessibility issues. To circumvent those data barriers that impede empirical research on gray markets, I adopt a novel approach for data collection and analysis. To that end, I study the gray market combating behavior of more than 3,000 public companies, company-by-company, for a period of twenty years. Then, using a collection of archival data sources I assemble a unique data set to use in my analyses. In chapter 3, I undertake the first empirical inquiry into the effect of gray market combating on firm performance and the contingencies that govern this effect. In chapter 4, I conduct a comprehensive review of the gray market combating mechanisms present in the literature, review available theoretic arguments about them, posit theoretical relationships, and conduct the first assessment of the financial efficacy of those different combating mechanisms. Then, I identify a number of firm-level factors that may drive the firm’s choice of gray market combating mechanism. The findings of these two studies address some long-standing, focal research questions in the gray market literature, provide managers with many valuable, actionable insights and recommendations, and put before policymakers some novel, revealing scientific evidence that may help them in dealing with the gray market controversy (e.g., whether the net impact of gray markets on firm performance and social welfare is benign or harmful, the necessity and/or merit of an active legislative role). The conclusion chapter closes this dissertation by reflecting on the new knowledge created by this research and highlighting its significance to theory, practice, and policymaking.
Keywords: Brand Equity; Distribution Strategy; Brand-Channel Interface; Gray Market; Grey Market; Parallel Importation; Marketing Strategy; Event Study; Distribution Channels; Gray Markets; Channel Management; Branding